Analisis Prosedur Pemeriksaan MRI Hip Joint pada Kasus AVN Menggunakan Flexible Coil - Nurul Syakirah; I Made Lana Prasetya; I Putu Surya Dharma Negara (KOLONI, 2026)
Avascular Necrosis (AVN) is a condition characterized by the death of bone tissue due to impaired blood supply, most commonly affecting the femoral head and potentially leading to progressive structural damage if not diagnosed at an early stage. Magnetic Resonance Imaging (MRI) is the preferred imaging modality for detecting AVN because of its high sensitivity in identifying bone marrow and soft tissue changes. At RSUD Bali Mandara, MRI examinations of the hip joint in AVN cases are performed using a flexible coil, making it necessary to evaluate the examination procedure and the resulting image quality. This study aimed to analyze the MRI hip joint examination procedure in AVN cases using a flexible coil and to assess the diagnostic value of the images produced. A descriptive qualitative research design was employed, with data collected through observation, interviews, and documentation involving two patients who underwent MRI hip joint examinations. The results showed that the examination procedure included patient preparation, equipment preparation, patient positioning, and image acquisition using multiplanar MRI sequences. Based on interviews with radiographers and radiologists, the use of a flexible coil produced images with low noise levels and sufficient quality to clearly demonstrate hip joint anatomy and AVN characteristics. In one patient, MRI revealed signal changes in the femoral head consistent with AVN, while the second patient showed imaging features more indicative of osteoarthritis. It can be concluded that the use of a flexible coil in MRI hip joint examinations provides diagnostically acceptable image quality and can support the diagnosis of AVN when combined with appropriate examination techniques and optimized imaging parameters.